PENGEMBANGAN INSTRUMEN ASESMEN AWAL DALAM MENINGKATKAN HASIL BELAJAR BERDIFERENSIASI ANAK USIA DINI - Risna H. Pakaya; Misran Rahman; Pupung Puspa Andini (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to develop an early assessment instrument that can be used to improve differentiated learning outcomes in early childhood, especially the age group of 5-6 years old in PAUD Dengilo District. The method used is research and development (R&D) with a mix-method approach, which combines qualitative and quantitative approaches. The research procedure includes needs analysis, product development, expert validation, limited trials, revisions, and extensive trials. Qualitative data was obtained through observation and interviews, while quantitative data was obtained from the results of pretest and posttest children's learning outcomes. The results of the study showed that the initial assessment instruments developed were valid (validity score of 92%), practical, and effective in identifying children's early abilities. After the application of the instrument in differentiated learning, there was a significant improvement in children's learning outcomes, which was shown by an increase in the average score from 67.8 to 83.2. The t-test showed a significance value of p < 0.05, which indicates a statistically significant difference. Thus, this initial assessment instrument can be used as a strategic tool for PAUD teachers in designing learning that suits the needs and potential of each child.